2022
DOI: 10.1073/pnas.2201250119
|View full text |Cite|
|
Sign up to set email alerts
|

Evolved interactions stabilize many coexisting phases in multicomponent liquids

Abstract: Phase separation has emerged as an essential concept for the spatial organization inside biological cells. However, despite the clear relevance to virtually all physiological functions, we understand surprisingly little about what phases form in a system of many interacting components, like in cells. Here we introduce a numerical method based on physical relaxation dynamics to study the coexisting phases in such systems. We use our approach to optimize interactions between components, similar to how evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…The constraints refer to concentrations that cannot change due to the nature of the system. If there are n ph possible coexisting phases, 240 then for fixed temperature and pressure, there are n df thermodynamic degrees of freedom in the system. This is estimated as n df = n am − n con − n ph .…”
Section: Extending To Complex Mixtures Of Macromoleculesmentioning
confidence: 99%
“…The constraints refer to concentrations that cannot change due to the nature of the system. If there are n ph possible coexisting phases, 240 then for fixed temperature and pressure, there are n df thermodynamic degrees of freedom in the system. This is estimated as n df = n am − n con − n ph .…”
Section: Extending To Complex Mixtures Of Macromoleculesmentioning
confidence: 99%
“…Biomolecular condensates arise via spontaneous and driven phase transitions of complex mixtures of multivalent protein and RNA molecules 15 . A key challenge is understanding how condensates with shared and distinct macromolecular compositions can coexist as distinct functional entities 6 ( Figure 1a ). The importance of this issue is emphasized by observations in the filamentous fungus Ashbya gossypii where Langdon et al, 7 reported the presence of coexisting ribonucleoprotein condensates that share the protein Whi3.…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, mixtures of phase-separating molecules can exhibit synergy or interference of LLPS. In general, multicomponent mixtures are more likely to separate in multiple coexisting phases and those phases are more robust to fluctuations in the number or concentration of components 5 . Nevertheless, a deeper understanding of LLPS and multiphase organization in complex mixtures is required, as protocell organization may underlie their function as reactors.…”
Section: Open Questions On Liquid–liquid Phase Separation For the Ori...mentioning
confidence: 99%